2018
DOI: 10.1177/0022034518797275
|View full text |Cite
|
Sign up to set email alerts
|

Berberine Ameliorates Periodontal Bone Loss by Regulating Gut Microbiota

Abstract: Postmenopausal osteoporosis (PMO) is a risk factor for periodontitis, and current therapeutics against PMO prevent the aggravated alveolar bone loss of periodontitis in estrogen-deficient women. Gut microbiota is recognized as a promising therapeutic target for PMO. Berberine extracted from Chinese medicinal plants has shown its effectiveness in the treatment of metabolic diseases such as obesity and diabetes via regulating gut microbiota. Here, we hypothesize that berberine ameliorates periodontal bone loss b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
93
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(105 citation statements)
references
References 41 publications
(54 reference statements)
7
93
0
Order By: Relevance
“…Of note, the current study showed that gavage-feeding of probiotics exerted no positive effects on the alveolar bone destruction in rats free of OVX or in ammatory state. This is consistent with our previous ndings of berberine or probiotics treatment outcome reported by others [41,78]. This may suggest the unnecessity of over-supplementation of probiotics in healthy population as also suggested by many researchers [79,80].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Of note, the current study showed that gavage-feeding of probiotics exerted no positive effects on the alveolar bone destruction in rats free of OVX or in ammatory state. This is consistent with our previous ndings of berberine or probiotics treatment outcome reported by others [41,78]. This may suggest the unnecessity of over-supplementation of probiotics in healthy population as also suggested by many researchers [79,80].…”
Section: Discussionsupporting
confidence: 93%
“…Although mechanisms are still unclear, bene cial local effects of probiotics on in ammatory alveolar bone loss have also been reported [38,[75][76][77]. Our previous study also shown that administration of berberine, a natural alkaloid with well-known ecological effect on gut microbiota, can enrich butyrate-generating bacteria and elevate the generation of gut-derived SCFAs, which promote gut barrier function and attenuate OVX-exacerbated periodontal bone loss [41]. Consistently, our current work found that the dysbiotic gut microbiota under estrogen-de ciency increased gut permeability with enhanced serum LPS, and the ensuing in ammatory responses skewed the distribution of Th17/Treg cells in the bone marrow and aggravated alveolar bone loss.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Butyrate is a short-chain fatty acid (SCFA) that has been used to treat metabolic disorders, such as obesity, insulin resistance, and postmenopausal osteoporosis [48,49] . It has been found that modulating the gut microbiome to increase butyric acid production can enhance the integrity and function of the intestinal barrier, thereby improving periodontal bone loss [50] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, data showed that berberine could attenuate the differentiation of osteoclasts and promote osteoblast differentiation in vitro [9]. In vivo experiments have shown that berberine can ameliorate periodontal bone loss and improve osteoporosis in some animal models [10][11][12][13][14]. However, it remains unknown whether berberine ameliorates obesity-induced bone damage.…”
Section: Introductionmentioning
confidence: 99%